Video-assisted thoracoscopic resection of lung nodules localized with a hydrogel plug. (21st February 2019) - Imperatori, Andrea; Fontana, Federico; Dominioni, Lorenzo; Piacentino, Filippo; Macchi, Edoardo; Castiglioni, Massimo; Desio, Matteo; Cattoni, Maria; Nardecchia, Elisa; Rotolo, Nicola
Abstract: OBJECTIVES: Computed tomography (CT)-guided hydrogel plug deployment was recently proposed for lung nodule preoperative localization and simultaneous prevention of pneumothorax. We analysed our initial experience with CT-guided hydrogel plug localization of lung nodules in patients undergoing video-assisted thoracoscopic (VATS) resection. METHODS: We retrospectively evaluated the medical notes from 27 consecutive patients (mean age 68 ± 11 SD years; men 74%) undergoing VATS lung wedge resection for biopsy or definitive treatment of 28 small pulmonary nodules (malignant 82%) at a single institution between October 2017 and July 2018. Difficult intraoperative nodule localization was anticipated with a lesion <10 mm, a depth from pleura:size ratio >1, ground-glass opacity or the judgement of the operating surgeon. All lesions were preoperatively marked by deployment of a CT-guided hydrogel plug. Study end points were frequency of postlocalization pneumothorax; feasibility of delayed surgery; rate of localization of intraoperative nodule and rate of successful VATS resection. RESULTS: The mean sizes of the solid nodules ( n = 24) and of the ground-glass opacities ( n = 4) were, respectively, 10.4 ± 3.4 mm and 16.0 ± 6.2 mm. One (4%) hydrogel plug marking procedure caused a clinically relevant pneumothorax. Nodule resection was scheduled flexibly as required by patient management/operating room scheduling: same day (11 nodules) or delayed [median 6 days (range 1–60 days)]; (17 nodules). All nodules were localized intraoperatively: 25 (89%) by hydrogel plug; 3 (11%) by palpation and pleural puncture hole visible after plug displacement. All nodules were completely excised by VATS, without complications. CONCLUSIONS: CT-guided hydrogel plug marking was valuable for VATS localization and resection of challenging lung nodules. The plug minimized clinically relevant pneumothoraxes and allowed flexible surgical schedules.